Business Aspects of Web Services - Weinhardt, Christof; Benjamin, Blau; Conte, Tobias; Neumann, Lilia; Meinl, Thomas; Michalk, Wibke (Springer Berlin Heidelberg Imprint: Springer, 2011)
Driven by maturing Web service technologies and the wide acceptance of the service-oriented architecture paradigm, the software industry?s traditional business models and strategies have begun to change: software vendors are turning into service providers. In addition, in the Web service market, a multitude of small and highly specialized providers offer modular services of almost any kind and economic value is created through the interplay of various distributed service providers that jointly contribute to form individualized and integrated solutions. This trend can be optimally catalyzed by universally accessible service orchestration platforms ? service value networks (SVNs) ? which are the underlying organizational form of the coordination mechanisms presented in this book. Here, the authors focus on providing comprehensive business-oriented insights into today?s trends and challenges that stem from the transition to a service-led economy. They investigate current and future Web service business models and provide a framework for Web service value networks. Pricing mechanism basics are introduced and applied to the specific area of SVNs. Strategies for platform providers are analyzed from the viewpoint of a single provider, and so are pricing mechanisms in service value networks which are optimal from a network perspective. The extended concept of pricing Web service derivatives is also illustrated. The presentation concludes with a vision of how Web service markets in the future could be structured and what further developments can be expected to happen. This book will be of interest to researchers in business development and practitioners such as managers of SMEs in the service sector, as well as computer scientists familiar with Web technologies. The book?s comprehensive content provides readers with a thorough understanding of the organizational, economic and technical implications of dealing with Web services as the nucleus of modern business models, which can be applied to Web services in general and Web service value networks specifically.